2020
DOI: 10.2147/ott.s255485
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hsa_circ_0001806 Acts as a ceRNA to Facilitate the Stemness of Colorectal Cancer Cells by Increasing COL1A1</p>

Abstract: Background: The aberrant expression of circular RNAs (circRNAs) has been identified as a novel trait of cancers. However, the role of circRNAs in colorectal cancer (CRC) remains to be elucidated. Methods: Informatic analysis was performed to identify circRNAs in CRC tissues and adjacent tissues. Gain-and loss-of-function experiments were constructed to analyze hsa_-circ_001806 roles in CRC cell stemness by sphere-formation, ALDH activity, stemness marker expression and tumor-initiating ability assays. CCK8 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Several recent studies have reported the oncogenic role of circ-CSPP1 in ovarian cancer, cervical cancer, glioma, and hepatocellular carcinoma [ 21 , 22 , 23 , 24 ]. Here, our work showed a remarkable overexpression of circ-CSPP1 in CRC, in agreement with the recent work [ 10 ]. Furthermore, we presented a significant clinical association of circ-CSPP1 with the poor prognosis of CRC patients.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Several recent studies have reported the oncogenic role of circ-CSPP1 in ovarian cancer, cervical cancer, glioma, and hepatocellular carcinoma [ 21 , 22 , 23 , 24 ]. Here, our work showed a remarkable overexpression of circ-CSPP1 in CRC, in agreement with the recent work [ 10 ]. Furthermore, we presented a significant clinical association of circ-CSPP1 with the poor prognosis of CRC patients.…”
Section: Discussionsupporting
confidence: 93%
“…Despite these studies, the precise actions of circRNAs in CRC development have remained unclear. circ-CSPP1 was recently identified as a circRNA whose overexpression in CRC contributed to the stemness of CRC cells [ 10 ]. Our current study expanded on this by identifying circ-CSPP1 as a crucial regulator in CRC cell malignant behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CircCSPP1 (hsa_circ_0001806, hsa_circ_001780) also is involved in the process of EMT and its high levels are associated with higher liver metastasis risk [ 153 ]. Wang et al, 2020 [ 154 ] explained the role of circCSPP1 in enhancing CRC cell migration and invasion by upregulation of COL1A1 (collagen, type I, alpha 1) expression from circRNA in a miR-193-5p-dependent way.…”
Section: Oncogenic Functions Of Circrnasmentioning
confidence: 99%